Supervision of the Performance of Education Personnel as an Effort to Realize Quality Education Service Standards - Oktaviani, Yeni; Hasbi, M.; Maryance (Journal of Quality Assurance in Islamic Education (JQAIE), 2024)
This study aims to evaluate the effectiveness of supervision of the performance of education personnel at SMP Negeri 11 Palembang by comparing the implementation of activities with the standards that have been set. Supervision in the context of education is known as supervision, where school supervisors have an important role in coaching and assessment both in academic and managerial aspects. In this study, the researcher uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research respondents included the Principal, Vice Principal, Administrative Staff, and Head of Library. Data analysis was carried out by data reduction techniques, data presentation, and conclusion drawn, and data validity tests using source triangulation and techniques. The results of the study show that supervision is carried out regularly and systematically, with a focus on timeliness, quality, quantity, and cooperation of education personnel. The principal directly monitors and compares the work results with the set standards, as well as provides feedback for performance improvement. The findings of the study reveal that the measurement of the implementation of activities plays an important role in maintaining the quality of performance, improving discipline, and creating a professional work culture. Supervision that is carried out well not only functions as an evaluation tool, but also as a means to increase the motivation and competence of education personnel. This study recommends that the supervision and measurement practices applied at SMP Negeri 11 Palembang can be adopted by other schools to improve the overall quality of education.